Artemisinin-Based Combination Therapy Depressed Mitosis and Induced Chromosome Aberration in Onion Root Cells - J. I. Raji; C. K. Onwuamah; P. G. C. Odeigah (Journal of Toxicology)
Artemisinin-based combination therapy is used to treat uncomplicated malaria disease in most endemic countries. Although most antimalarial drugs are effective in killing the parasite, there is a concern of induced toxicity to the cell. Here, the cytogenotoxicity of dihydroartemisinin-piperaquine phosphate (DHAP), a coformulation for artemisinin-based combination therapy, was evaluated using Allium cepa model. The toxicity on the mitotic index varies with the duration of exposure and dose tested. Chromosome aberrations observed include chromosome fragments, chromosome bridges, binucleated cells, and micronucleated cells. This study showed that DHAP can depress mitosis and induce chromosome abnormalities. Their accumulation in cells may be inhibitory to cell division and growth. This calls for caution in the administration of artemisinin combination therapy for the treatment of malaria ailment. Wide spacing of dosage is therefore suggested in order to avoid the risk of genetic damage.